Enhanced P-wave velocity imaging by marine airgun-source seismic surveys with distributed acoustic sensing - Shun Fukushima; Masanao Shinohara; Tomoaki Yamada; Ryota Hino; Ryosuke Azuma; Yoshihiro Ito; Yusuke Yamashita; Hiroki Takano (Scientific Reports)
Abstract P-wave velocity (Vp) structures in marine areas have been estimated using marine airgun-source seismic surveys and refraction methods. The lateral resolution of Vp structures depends on the number of receivers and shots. In marine environments, Vp resolution is often limited due to the sparse distribution of ocean bottom seismometers (OBSs). Recently, distributed acoustic sensing (DAS) offers a cost-effective alternative, providing high-density strain measurements along optical fiber cables. This study demonstrates that seismic refraction using DAS data is effective for imaging shallow Vp structures with high lateral resolution. A seismic survey was conducted using R/V Hakuho-maru, airgun sources, and DAS and OBS measurements along a seafloor optical fiber cable off Sanriku, Japan. Strong lateral heterogeneities in the Vp structure were observed, due to the dense spatial sampling of DAS data. The two-dimensional Vp structure obtained from the DAS data showed good agreement with the seismic reflection profile. This experiment highlights the unique advantages of DAS data over OBSs for seismic refraction.